"EDG 6931 Writes Back!" Black Studies as Emancipatory Resistance to Neoliberal Tyranny in Teacher Education. (June 2017) - Acosta, Melanie M.
Academics have a responsibility to raise human consciousness and make connections to those elements of power and politics often hidden from public view, yet the strong arm of neoliberalism has tightened its grip on the structure, and scope of higher education and this includes the moral rigor of teacher education courses. Therefore, emancipatory learning spaces are critical to the development of competent and conscious educators. This article presents one example of the transformative possibilities in learning to teach that emerges from the emancipatory pedagogy of Critical Studyin'. The article includes student work from one course assignment as an example of Critical Studyin' in action to highlight the kinds of critical knowledge students can acquire when learning to teach is situated as a morally engaged endeavor. The article concludes with implications for teaching and learning to teach in neoliberal times.